Linewidths in energy-resolved two-photon photoemission spectroscopy - Boger, Klaus; Roth, Manfred; Weinelt, Martin; Fauster, Thomas; Reinhard, Paul-Gerhard (Physical Review B, 2002)
Energy-resolved two-photon photoemission is modeled in the framework of optical Bloch equations for a three-level system. For pulsed excitation, analytical expressions for the photocurrent have been derived which elucidate numerical solutions. The information that can be extracted from linewidth analysis is demonstrated to depend substantially on the shape of pump and probe pulses. The analysis is applied to image-potential states leading to overall good agreement.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.IAP.LF.linewi